# Which equation is not in proper form for using the zero-factor property? Why? A. (x + 2)(x-6) = 0 C. 3t(t + 8) (t- 9) = 0 B. x(3x - 7) = 0 D. y(y - 3) + 6(y -

Which equation is not in proper form for using the zero-factor property? Why?

**Transcribed Image Text:**

## A. (x + 2)(x-6) = 0 C. 3t(t + 8) (t- 9) = 0 B. x(3x - 7) = 0 D. y(y - 3) + 6(y - 3) = 0

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

- Tutor Answer

## The equation that is not in proper form for using the zerofactor property is D yy 3 6y 3 0 The zerof…View the full answer

**Related Book For**

## Intermediate Algebra

**ISBN:** 9780134895987

13th Edition

**Authors:** Margaret Lial, John Hornsby, Terry McGinnis

**Question Details**

Chapter #

**5**Section: Mixed Review Exercises

Problem: 10

**Posted Date:**June 04, 2023 01:42:51

## Students also viewed these Mathematics questions